Comparing the effectiveness of two occupational therapy stroke upper limb home programmes - Chhania, Bhavika Harrilal (My University, 2015)
OTs treat stroke patients more than any other diagnostic group, thus it is essential to find ways in making therapy most effective. The benefits come from assisting the brain to reorganize itself through rehabilitation, which in turn helps the stroke patient to recover lost functions after brain damage.The desire to understand what types and intensities of rehabilitation strategies result in optimal and cost effective outcomes has been a stirring force behind research. There is mounting evidence that intervention strategies providing meaningful engagement, context relevant, in activities are more advantageous for skill achievement than rote exercise/passive modalities. Thus OTs should consider this in all aspects of their treatment. Patients are known not to be compliant with their exercises; therefore it is essential that home programmes contain more activities that they would do normally at home, which will ensure more compliancy. This study aims at comparing the effectiveness of a TEHP and a TOHP on the improvement of upper limb function through measurement with the DASH. This will guide OTs in their future designs of home programmes. The controlled (TEHP) and experimental group (TOHP) both consisted of 22 participants each who were assessed using the DASH upon discharge after receiving OT intervention. Thereafter the patients were reassessed upon follow up, which was within 4 weeks post discharge. The mean discharge and follow up scores of both groups were compared. Both groups had better DASH scores upon follow up; however, the experimental group yielded a statistically significant difference in the overall DASH score. The study indicates that the use of a TOHP, consisting of more of activities of daily living may have a greater impact on independence than the use of a TEHP in the treatment of acute stroke patients.
A research report submitted in partial fulfillment of the requirements for the degree Masters of Science in Occupational Therapy to the Faculty of Health Sciences, School of Therapeutic Sciences, Wits University, Johannesburg April 2015